Criminal Liability of Child Abuse Perpetrators in Daycare: An Islamic Criminal Law Perspective - Nastania, Ani Ridho Sari; Aldi; Riduan, Hafiz; Maulana, Apriansya; Novita, Melvi; Saputra, Andika (Yayasan Bina Lentera Insan, 2026)
Child abuse in daycare centers constitutes a violation of children's rights to protection and proper care. This study aims to analyze the criminal liability of perpetrators of child abuse in daycare centers from the perspective of Islamic criminal law. The research employs a normative legal method with a library research approach. Data were collected through documentation and literature review of relevant primary and secondary legal sources and were analyzed using a descriptive qualitative method. The findings indicate that violence against children, whether committed intentionally or through negligence, constitutes a jarimah (criminal act) that is contrary to the objectives of Islamic law (maqashid al-shari'ah), particularly the protection of life (hifz al-nafs) and lineage (hifz al-nasl). Perpetrators may be held criminally liable through the application of qisas, diyat, or ta'zir sanctions according to the degree of fault and the consequences of their actions. Therefore, criminal liability in Islamic law serves not only as a means of punishment but also as an effort to protect children's rights and prevent violence in daycare environments.